Sustainable Labelling on Packaging: Does It Impact Purchase Behavior? - Misron, Aervina; Musa, Normaziah Che; Salleh, Muhammad Syafiq; Zandi, GholamReza (International Review of Management and Marketing, 2025)
The purpose of this paper is to identify and empirically examine the impact of perceived behavior control, openness to experience and conscientiousness on the purchase behavior of sustainable labelling products. Additionally, this study also investigates the role of purchase intention as a potential mediating variable on the relationships between independent and dependant variables. The study develops a set of hypotheses that are tested through a survey of 164 consumers, which are working adults in Malaysia. The hypothesized model is tested through structural equation modelling, using a statistical software, Smart-PLS version 4. The results indicated that perceived behavioral control and conscientiousness significantly influence purchase behavior of the consumers. Moreover, purchase intention is found to be significantly mediated the relationship between openness to experience and purchase behavior as well as conscientiousness and purchase behavior. The study highlights the valuable insights for management by providing recommendations to companies and decision-makers aiming to promote sustainable purchasing.